Transcription unit mapping in adenovirus: regions of termination. - Iwamoto, S (1986)
Using a series of single-stranded clones of adenovirus DNA, we determined the extent of RNA polymerase II transit early in infection for two rightward-reading transcription units. RNA synthesis beginning at the major late promoter (16.5 on the genomic map) continued until approximately 65 to 70 map units so that differential choices of mRNAs within that region were not based primarily on transcriptional decisions but rather on posttranscriptional decisions. Transcription from the major late promoter beginning at 16.5 map units, however, did greatly decrease before approximately 75 map units, ensuring that no mRNAs were formed with sequences beyond approximately 75 map units. Early transcription from E3 then began just past 75 map units (at a higher rate than transcription from the major late promoter); E3 transcripts terminated at least 2 kilobases downstream from a second and final poly(A) site in this transcription unit. The effectiveness of termination in E3 was greater than 95 to 99%.